2009
DOI: 10.1111/j.1365-2133.2009.09548.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision of skin cancer: the importance of training

Abstract: Background Skin cancers are the most common malignancy in New Zealand and their treatment imparts a huge burden on the healthcare system both in terms of the cost of surgical intervention and in treatment delivery (estimates are in excess of NZ$33 million per annum for the year 2000). Currently in New Zealand, skin cancers are excised by dermatologists, general practitioners (GPs), GPs with a special interest in skin surgery (GPSIs) and specialist surgeons with diverse training backgrounds including ear, nose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 20 publications
(24 reference statements)
3
20
0
3
Order By: Relevance
“…A total of six studies (Table ) were identified as suitable for inclusion in the present review, as outlined in the PRISMA diagram (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of six studies (Table ) were identified as suitable for inclusion in the present review, as outlined in the PRISMA diagram (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…). Three studies analysed efficacy of GPwSIs with regard to surgical excision of skin lesions. One study looked at the economic evaluation of a GPwSI‐led dermatology service in primary care and included GPwSIs carrying out skin excisions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standards are usually not monitored except by audit of individual doctors, with training generally being informal 'peer to peer' learning, with occasional continuing medical education activities. 2,3 and other countries [4][5][6][7] have shown that skin specialists diagnose and excise skin cancers better than GPs. GPs may unnecessarily remove benign lesions or, because of cost barriers for some patients, refer minor lesions to hospital clinics, placing a high demand on these services.…”
Section: Background and Assessment Of Problemmentioning
confidence: 99%
“…In Australia, GPs have long managed the majority of BCCs and SCCs . However, comparability of GP‐delivered with specialist‐delivered skin cancer management (or particular aspects of management) remains uncertain …”
mentioning
confidence: 99%